eBrain Computer-Interfaces: Conceptualization, Redesign Challenges and Social Impact - Alonso-Valerdi, L. M.; Arreola-Villarruel, M. A.; Argüello-García, J. (Revista Mexicana de Ingenieria Biomedica, 2019)
Brain-Computer Interfaces (BCIs) record the neural activity of the Central Nervous System, and then, produce ou-tputs that replace, restore, increase, supplement or improve the natural outputs of such system. Therefore, the interaction between the human beings and their internal or external environment is tranformed. However, over a century being investigated under laboratory conditions, BCIs have not been able to be transferred to the real world. This review aims to: (1) thoroughly understand the structure of a BCI and the system types, (2) analyze the challen-ge that the scientific community is facing to improve the interaction between user and system from the perspective of the engineering of human factors; and (3) describe the application of this type of assistive technology under development in the Mexican Society. The future of this technology and its effectiveness seem to depend more than ever on factors related to the user subjective perception, and the user adaptation to the system.